Counting days is a spacing incentive that unlocks the potential of low GPA students - Iman YeckehZaare; Paul Resnick (npj Science of Learning)
Abstract Spacing and retrieval practice enhance learning, but students often underuse these strategies. We tested a simple grading incentive, which we call Counting Days, in two RCTs: one randomizing 143 students within a course and another randomizing 71 instructors. The “counting questions” control condition awarded points for each practice question answered, while the “counting days” treatment assignment awarded points for each day that a student answered a set of questions. In the within-class experiment, the counting days group earned higher exam scores, mediated by spacing practice over more days. Spacing was especially beneficial for lower-GPA students: the correlation between course exam scores and GPA in prior courses was significantly lower for the counting days group. In the between-instructor experiment, there was no way to compare learning outcomes between instructors, but both the number of days and a number of questions practiced were significantly higher under the counting days condition.